Persistence of Cypermethrin, Deltamethrin and Endosulfan in an Oil Palm Agroecosystem - Ma, Choon Kwong (2002)
A study on the persistence of cypermethrin, deltamethrin and endosulfan in an oil palm agroecosystem was conducted at a Sime Darby estate in Sungai Buloh, Selangor. Three experimental plots in the estate were sprayed with cypermethrin, deltamethrin and endosulfan, respectively. The insecticides were sprayed using a motorized mist blower at the manufacturer's recommended dosage and double the recommended dosage. The application was conducted in triplicate plots. Composite soil samples were collected from each replicate plot at 0-10, 10-20, 20-30, 30-40 and 40-50 em depth. Palm fronds were randomly harvested from the plots and water samples were collected from the adjacent streams and drains along the plots. The insecticide residues in soil, water and palm leaves were monitored at 1, 3, 7, 14, 30, 60 and 90 days after treatment. Analytical methods for endosulfan, cypennethrin and deltamethrin residues were evaluated and good recoveries were observed for the matrices examined. A gas chromatograph equipped with an electron capture detector was used to quantify the pesticide concentrations in the extracts. Endosulfan was more persistent than deltamethrin and cypennethrin in the soil, with halflives of 38, 5 and 2 days, respectively. The corresponding values for palm leaf were 9, 4 and 6 days. None of the insecticides studied was found leached beyond 10 cm of the soil profile. Residue concentrations of the insecticides in soil and palm leaf were in the .range of 0.001 to 0.l9 mg/kg and 0.001 to 2.40 mg/kg respectively. Surface runoff of the insecticides however, was not evident in the agroecosystem as no residues were detected in the surface waters from adjacent drains and streams. The usefulness of two computer models, VARLEACH and PERSIST in predicting the fate of the insecticides in oil palm agroecosystem was assessed by comparing the field data with predicted data. Predictions with VARLEACH gave better agreement with observed insecticides residues than PERSIST. VARLEACH predicted cypennethrin, de1tamethrin and endosulfan did not leach beyond 10 cm of the soil profile, which was in agreement with the field observation.